ANALYSIS OF THEFT SANCTIONS: A COMPARISON OF INDONESIAN POSITIVE LAW, ISLAMIC CRIMINAL LAW, AND MUHAMMAD SYAHRUR'S CONTEMPORARY PERSPECTIVE - Mia Fitriah Elkharimah (State Islamic University Datokarama Palu, 2025)
This study compares theft sanctions in the Indonesian Criminal Code (KUHP), classical Islamic criminal law, and Muhammad Syahrur’s Theory of Hudud. The findings show fundamental normative and practical differences among the three systems. KUHP emphasizes flexibility, rehabilitation, and human rights, while classical Islamic law stipulates strict hudud amputation under very specific conditions. Syahrur offers a contextual reinterpretation by viewing amputation as the maximum limit, allowing alternative sanctions such as imprisonment or fines that remain within sharia boundaries. His approach provides a more humane and adaptable model suitable for Indonesia’s pluralistic legal context. Although Syahrur’s theory is widely appreciated in theft cases, its broader application in other areas of Islamic law remains controversial. This study contributes to ongoing efforts to harmonize divine principles with modern legal and human rights standards.